The survival analysis of tunnel-cuffed central venous catheter versus arteriovenous hemodialysis access among elderly patients: A retrospective single center study. (December 2020) - Raksasuk, Sukit; Chaisathaphol, Thanet; Kositamongkol, Chayanis; Chokvanich, Wittawat; Pumuthaivirat, Pratya; Srithongkul, Thatsaphan
Abstract: Background: There is currently a controversy for the optimal vascular access option in the elderly, regarding their multiple comorbidities and life expectancies. Our study aimed to compare the survival of tunneled cuff venous catheter (CVC) and arteriovenous access (AV access) in elderly patients. Methods: A retrospective cohort study was performed by electronic medical record review. All hemodialysis patients aged 65 years and over who firstly initiated dialysis from January 1, 2012 to December 31, 2016 at Siriraj hospital, Thailand, were included. The primary outcomes are to compare a 2-year period of survival between CVC and AV access in terms of abandonment, death, and combined outcome. Propensity score covariate and Charlson Comorbidity Score (CCI) were used for multivariable analysis adjustment. Results: A total of 359 patients were included; 216 (60.2%) patients had initiated hemodialysis via CVC while the rest used AV access. The patients' average ages were 76.7 ± 7.0 and 74.0 ± 5.8 years (p-value<0.001) in the CVC and AV access group, respectively. The 2-year mortality rates of CVC and AV access groups were 24.1% and 15.4%, respectively (p-value = 0.038). Multivariable analyses showed that the adjusted hazard ratio (aHR) of combined endpoints, i.e., vascular access abandonment and death, was statistically different only in the CCI-adjusted model (aHR = 0.68, 95% CI: 0.46–0.99). Mortality from infection cause was more common in the CVC group than the AV access group. Conclusion: CVC access maybe considers an alternative option for frail elderly patients. However, the patient selection is a crucial issue, given higher infection-related mortality in patients using CVC. Highlights: Central venous catheter maybe not inferior to AV access in extreme-age and frail elderly hemodialysis patients. Infection is still the concerning issue in patients using central venous catheter, which increased infection-related mortality and abandonment. Evaluating the optimal vascular access in elderly patients need further holistic aspects prospective studies.